Consistent Total Traction Torque-Oriented Coordinated Control of Multimotors with Input Saturation for Heavy-Haul Locomotives - Changfan Zhang; Qian Zhang; Jing He; Jianhua Liu; Xingxing Yang; Songan Mao (Journal of Advanced Transportation)
In the coordinated control of multiple motors for heavy-haul locomotives, the input value for a motor often exceeds its maximum allowable input value, resulting in the saturation problem. A traction total-amount coordinated tracking control (TACTC) strategy is proposed to address the input saturation of heavy-haul locomotives driven by multiple motors. This strategy reduces control input and suppresses input saturation. First, a multimotor traction model with uncertain parameter perturbations and external disturbances was established. Next, a sliding-mode disturbance observer (SMDO) was designed to reduce the sliding-mode switching gain, thereby decreasing the control input. An auxiliary anti-windup (AW) system was used to weaken the effect of input saturation on tracking performance. Then, the observed value and auxiliary state were fed back to the sliding-mode controller to design a TACTC protocol and ensure that the total amount of traction torque follows the desired traction characteristic curve. Finally, the Matlab/Simulink simulation and RT-Lab semiphysical experiment results show that the proposed strategy can effectively suppress the input saturation problem of multimotor coordinated control.